TRANSLATION COMPETENCE AND TRANSLATING PROBLEMS OF STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM SRIWIJAYA UNIVERSITY - Alhenri Wijaya (Politeknik Negeri Sriwijaya, 2019)
This study aims to find out the level of translation competence of the students of English Education Study Program of Sriwijaya University, to find out the strategies used by the students in translating texts from Indonesian to English and to identify the problems they encounter in translating texts. There were 36 students taken as the sample. A descriptive method was used in this study. The data were obtained by means of questionnaires, task, and interview. The findings showed that the subjects demonstrated pretextual level of translation competence. Spelling is accurate; source text is fully translated (only a few subjects did not translate it fully); text is long and strung-out because of use function words rather than lexicalizations; vocabulary is not varied; translation is structurally very close to the source text; and style is more “verby”. The findings of this study showed that most subjects tried to identify the main idea of the text before beginning to translate. They tried to understand the meaning of the words from the context first. If they could not grasp the meaning of that words, they consulted monolingual dictionaries, but if still did not get the meaning, they then looked for the words in bilingual dictionaries. Some of them did it the opposite. The findings of this study showed that most subjects thought that vocabulary, sentence structure, and word choice were the most difficult problems for them when translating. Some of them got problems when translating due to their knowledge background of the text to be translated and culture involved in the text.